M2 macrophage marker chitinase 3-like 2 (CHI3L2) associates with progression of conventional renal cell carcinoma - Pusztai, Csaba; Yusenko, Maria V.; Banyai, Daniel; Szanto, Arpad; Kovacs, Gyula (Anticancer research, 2019)
Background/Aim: In spite of early detection, appoximately 15% of the small renal cell carcinomas (RCC) will develop metastasis within 5 years follow-up. The aim of this study was to identify new biomarkers to estimate the postoperative relapse of the most common conventional RCC. Patients and Methods: Tissue multi arrays of conventional RCC without metastasis at the time of operation from a cohort of 634 patients were analysed by immunohistochemistry for expression of the chitinase 3-like protein 2 (CHI3L2). Cancer specific survival of patients was estimated with Kaplan-Meier analysis, univariate and multivariate Cox regression models. Results: Kaplan-Meier analysis estimated a shorter cancer-free survival for patients with CHI3L2 positive tumors. In multivariate analysis, the CHI3L2 positivity associated with a 3.5 times higher risk for tumor relapse (p<0.001). Conclusion: Expression of CHI3L2 in tumor cells of conventional RCC define a group of patients at high risk for postoperative progression.